Meningkatkan Kemampuan Mengenal Huruf Melalui Permainan Magic Paper Pada Anak Usia 5-6 Tahun di TK Mutiara - Masripah, Dede; Elnawati, Elnawati; Maulana, Redi Awal (PT Alahyan Publisher Sukabumi, 2026)
The ability to recognize letters is one of the important aspects in early childhood language development which is the basis for reading and writing skills at the next level of education. Based on the results of initial observations at Mutiara Kindergarten, it was found that the ability to recognize letters for children aged 5-6 years is still not optimally developed. This can be seen from some children who are not able to name letters, recognize the shape of the letters, and connect the letters with their sounds. Therefore, an interesting learning effort is needed and in accordance with the characteristics of early childhood, one of which is through the game of Magic Paper. This research aims to improve the ability to recognize letters through the game of Magic Paper in children aged 5–6 years in Mutiara Kindergarten. The research method used is Class Action Research (PTK) which is carried out in two cycles, where each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The subjects of the study were children in the age group of 5–6 years at Mutiara Kindergarten. Data collection techniques are carried out through observation, documentation, and performance assessment, while data analysis is carried out descriptively, qualitatively, and quantitatively. The results of the study show that the application of the Magic Paper game can improve children's letter recognition skills. In the initial condition (pre-cycle), the child's ability to recognize letters is still in the undeveloped category. After the action was carried out in the first cycle, there was an increase in the child's ability to pronounce and recognize letters, but had not yet reached the success indicator. Furthermore, in cycle II, the child's ability to recognize letters increased significantly and achieved the criteria of developing very well. Thus, it can be concluded that the Magic Paper game is effective in improving the ability to recognize letters in children aged 5–6 years in Mutiara Kindergarten.